2015
DOI: 10.1364/josab.32.001214
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical characterization of on-chip buckled dome Fabry–Perot microcavities

Abstract: Abstract:We report on the thermo-mechanical and thermal tuning properties of curved-mirror Fabry-Perot resonators, fabricated by the guided assembly of circular delamination buckles within a multilayer a-Si/SiO2 stack. Analytical models for temperature dependence, effective spring constants, and mechanical mode frequencies are described and shown to be in good agreement with experimental results. The cavities exhibit mode volumes as small as ~10 3 , reflectance-limited finesse ~3x10 3 , and mechanical resonan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…However, there are few options that promise fully monolithic integration of tunable high-finesse, open access microcavities on chips. Our group has reported a thin-film buckling approach [ 15 , 16 , 21 , 88 ] with potential to address this latter point. We’ve shown that circular delamination buckles can be controllably formed within a multilayer thin film stack, and that these features can behave as half-symmetric Fabry-Perot cavities.…”
Section: Fpcs For Cavity Quantum Electrodynamics Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are few options that promise fully monolithic integration of tunable high-finesse, open access microcavities on chips. Our group has reported a thin-film buckling approach [ 15 , 16 , 21 , 88 ] with potential to address this latter point. We’ve shown that circular delamination buckles can be controllably formed within a multilayer thin film stack, and that these features can behave as half-symmetric Fabry-Perot cavities.…”
Section: Fpcs For Cavity Quantum Electrodynamics Applicationsmentioning
confidence: 99%
“…Others have employed wafer-bonding approaches combined with precision alignment stages [ 14 ]. However, the realization of truly monolithic, curved mirror FPCs with high F and low V M remains at a relatively nascent stage of development [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are few options that promise fully monolithic integration of tunable high-finesse, open access microcavities on chips. Our group has reported a thin-film buckling approach [15,16,20,86] with potential to address this latter point. We've shown that circular delamination buckles can be controllably formed within a multilayer thin film stack, and that these features can behave as half-symmetric Fabry-Perot cavities.…”
Section: Chip-based Fpcs For Cqedmentioning
confidence: 99%
“…Others have employed wafer-bonding approaches combined with precision alignment stages [14]. However, the realization of truly monolithic, curved mirror FPCs with high F and low Vm remains at a relatively nascent stage of development [15,16].…”
Section: Introductionmentioning
confidence: 99%